Efficacy and safety of per-oral endoscopic myotomy for the treatment of Achalasia Cardia in Malaysia: a single centre study - Nik Muhamad Affendi, Nik Arsyad; Ho, Shiaw Hooi; Peng Choong, lau; Mahadeva, Sanjiv (Wiley, 2021)
Background and Aim: Peroral Endoscopic Myotomy (POEM), introduced in 2010, has become a widely accepted treatment for achalasia cardia. How- ever, POEM procedure is technically challenging and recommended to be performed by experienced endoscopists. Our objective was to assess the ef- ficacy and safety of POEM procedures performed in a tertiary referral cen- tre. Methods: This is a retrospective single-centre study. All consecutive achalasia patients that underwent POEM procedure (posterior approach) from November 2015 to May 2021 were recruited. Demographic data, acha- lasia type, technical success, procedure duration, myotomy length, duration of hospital stay, clinical success and adverse events were recorded. Techni- cal success was defined as completion of POEM procedure from mucosa in- cision, to tunnel creation followed by myotomy and finally, mucosal closure. Clinical success was defined as a post-procedure Eckardt score ≤3, or a reduction of 4 or more points at 2 months or more after a successful procedure. All POEM procedures were performed by 3 endoscopists (2 gas- troenterologists and 1 surgeon) who have had experience in ESD or Heller’s myotomy. Results: A total of 65 patients were recruited. The detailed results are summarised in Table 1. Conclusion: The high efficacy (with good inter- mediate to long-term outcome follow up) and good safety profile of the POEM procedure for achalasia cardia in our centre are comparable with the published literature. Adverse events were generally mild, and all were managed conservatively. The improvement seen in the technical success rate after the first 20 cases is in line with mastering the POEM skill after the initial learning experience.